ESTUDO DA ABSCISÃO DE FRUTOS DA LARANJEIRA NATAL (Citrus Sinensis OSBECK) NA FASE DE PRÉ-COLHEITA - Moreira, Cristina Drummond; Moreira, Célio S.; Sarriés, Gabriel A. (REVISTA DE AGRICULTURA, 2015)
ESTUDO DA ABSCISÃO DE FRUTOS DA LARANJEIRA NATAL (Citrus Sinensis OSBECK) NA FASE DE PRÉ-COLHEITA